Pengaruh Fixed Asset Rasio, Return On Asset, Firm Size, Dan Working Capital Turnover Terhadap Struktur Modal Pada PT. Aneka Gas Industry Tbk - Yuni Yuni; Mukhlis Mukhlis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to find out whether the Fixed Asset Ratio, Return On Assets, Firm Size, and Working Capital Turnover have an influence on the Capital Structure of PT. Aneka Gas Industry Tbk. This type of research is associative research with a quantitative approach. The population and sample used in this research are the financial reports of PT Aneka Gas Industry Tbk for the period 2014 - 2022 or for 9 years which were obtained using a saturated sampling technique. The data collection technique used in this research uses documentation techniques and literature study. The data source used in this research is a secondary data source obtained from the official website of the Indonesian Stock Exchange www.idx.co.id. The data analysis techniques used in this research are the classical assumption test, multiple linear analysis, coefficient of determination test, t test, and f test. The results of this research show that partially the Fixed Asset Ratio (X1) does not have a significant influence on Capital Structure (Y), partially Return On Assets (X2) does not have a significant influence on Capital Structure (Y), partially Firm size (X3) does not has a significant influence on Capital Structure (Y), and Working Capital Turnover (X4) partially does not have a significant influence on Capital Structure (Y). Meanwhile, simultaneously Fixed Asset Ratio, Return On Assets, Firm Size, and Working Capital Turnover have a significant influence on the capital structure of PT. Aneka Gas Industry Tbk.